2018
DOI: 10.1111/beer.12210
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of peers’ unethical behavior on employees’ ethical intention: Moderated mediation by Machiavellian orientation

Abstract: Research suggests a direct negative relationship between peers’ unethical behavior and employees’ ethical intention. But several possible mechanisms might explain this relationship in more detail. For example, Machiavellianism is a personality trait characterized by interpersonal manipulation and the use of unethical means to achieve certain self‐interested ends, whether useful or pleasant. This article adopts an Aristotelian understanding of philia, related to three goods on which human relationships rest: us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 156 publications
(273 reference statements)
1
26
1
Order By: Relevance
“…On the other hand, peers' self-interest and unethical behaviors are expected to harm HAW. In a recent study, Ruiz-Palomino et al (2019) found that peers' unethical behavior increased the negative impact of self-interest (Machiavelianism) on employees' ethical intentions. They also showed that when peers' unethical behavior is not present, the negative effect of selfinterest on ethical intentions disappears.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, peers' self-interest and unethical behaviors are expected to harm HAW. In a recent study, Ruiz-Palomino et al (2019) found that peers' unethical behavior increased the negative impact of self-interest (Machiavelianism) on employees' ethical intentions. They also showed that when peers' unethical behavior is not present, the negative effect of selfinterest on ethical intentions disappears.…”
Section: Resultsmentioning
confidence: 97%
“…When the opportunity to observe others' behaviors is not easy, using reports from others is likely not to be more appropriate than using self-reports (Podsakoff et al, 2012), given that on certain occasions, individuals are the most aware of their own personal behavior (Ruiz-Palomino et al, 2019). Thus, to measure this variable, we slightly adapted a 12-item scale used in previous research (Newstrom and Ruch, 1975;Ferrell and Weaver, 1978) and asked employees to assess their level of agreement on these 12 items, which were a faithful reflection on what ethical behavior is, that is, behavior that rests upon universal moral principles leads to human growth (Ruiz-Palomino et al, 2019) and helps to ensure the good functioning of the organization (Ko et al, 2018). We combined the responses to each of the 12 items linearly to form a Mode A first-order composite variable, such that higher scores indicated stronger employee ethical behavior.…”
Section: Employee Ethical Behaviormentioning
confidence: 99%
“…Relativism scores relate positively with Machiavellianism (e.g., r = .319, Al‐Khatib, Malshe, & Abdulkader, ; r = .45, Gurbuz & Eris, ; r = .328, Ho, Vitell, Barnes, & Desborde, ). Decades of research have confirmed that high Machiavellians are manipulative (Austin, Farrelly, Black, & Moore, ), regularly tell lies (McLeod & Genereux, ), intend to behave in ethically questionable ways (Ruiz‐Palomino, Banon‐Gomis, & Linuesa‐Langreo, ), adhere to questionable social norms (Shafer & Wang, ), and engage in destructive behaviors at work (Galperin, ). Although questionable ethics among Machiavellians suggest the same about high relativists, the implications of high Machiavellianism here may not be so straightforward.…”
Section: Additional Potential Insights From Item‐level Relationshipsmentioning
confidence: 99%